The class according to what has been established in Cuban ministerial regulations - Zenén Rodríguez Fernández; Lilia Esperanza Chércoles Cazate; Francisca de las Nieves Santisteban Aguilera; José Manuel Ricardo Ramírez; Manuel Esteban Uriarte Gómez (Centro Provincial de Información de Ciencias Médicas, 2017)
In spite of its improvement from the technological point of view and of the widespread implementation of active methods of teaching, the class constitutes a tangible problem that is evidenced mainly during the professors promotion to other teaching categories, in their unawareness on the different types of classes and in their role in higher medical education, reason why a critical documental review of the existing legislation was carried out with the objective of its conceptualization.  It was concluded that the class in all its varieties constitutes a form of outstanding organization of the teaching educational process and its function is fundamental in linking study with work and instruction with education, with the purpose of obtaining cultured, competent, independent and creative professionals, so that they can perform  successfully either inside or outside the country.